Advanced fitness assessment and exercise prescription. - Heyward, Vivian H., ....- (Champaign : Human Kinetics, 2010)
Unique in its scope, depth of content, organization, and approach to the subject matter, the sixth edition of Advanced Fitness Assessment and Exercise Prescription will assist exercise science students and practitioners in bridging the gap between research and practice. Built around physical fitness components, this text shows readers first how to assess each component and then how to design exercise programs based on that assessment. Advanced Fitness Assessment and Exercise Prescription synthesizes concepts and theories from exercise physiology, kinesiology, measurement, psychology, and nutrition to provide a clearly defined approach to physical fitness testing and the design of individualized exercise programs. Unlike other introductory texts, which typically focus on field testing for evaluating physical fitness, this text includes both field and laboratory assessment techniques. This user-friendly text offers the latest physical activity and exercise recommendations for health benefits
Weight loss, and weight maintenance as well as practical guidelines for designing individualized exercise programs for your clients. Readers will find the latest information on maximal and submaximal graded exercise testing in healthy populations, muscular fitness testing protocols and norms for children and adults, and field tests and norms for evaluating cardiorespiratory fitness, muscular fitness, body composition, flexibility, and balance. The sixth edition of Advanced Fitness Assessment and Exercise Prescription presents updated content throughout, including new guidelines for exercise testing and prescription from the 2010 edition of ACSM's Guidelines for Exercise Testing and Prescription, plus new physical activity recommendations from the U.S. government, American Dietetic Association, and the American Heart Association. Several topics have also been added or expanded to include updated information on * using new technologies-including global positioning systems (GPS), geographic
Information systems (GIS), interactive video games (such as Wii), and persuasive technology-to promote physical activity and to change exercise behaviors; * behavior change theories and models, including the health belief model, decision-making theory, theory of reasoned action, theory of planned behavior, and self-determination theory; * certification and licensure of exercise science professionals; * OMNI pictorial scales for assessing ratings of perceived exertion of adults and children; * exercise recommendations for preventing low back pain from the North American Spine Society; * and assessing balance and designing balance programs (new chapter). Advanced Fitness Assessment and Exercise Prescription begins with an overview of physical activity, health, and disease. Next, preliminary health screening, risk classification, and the principles of fitness assessment, exercise prescription, and exercise program design are discussed. The remainder of the text provides in-depth
Coverage of assessment and exercise prescription for each of five physical fitness components: cardiorespiratory endurance, muscular fitness, body weight and composition, flexibility, and balance. Within each chapter, key questions alert readers to essential information, while key points, review questions, and key terms reinforce important concepts and content. For instructors, online access to an instructor guide, test package, and presentation package provides helpful tools for lecture preparation, creative content delivery, and class assessment. By integrating the latest research, recommendations, and information into direct and clear guidelines for application, the sixth edition of Advanced Fitness Assessment and Exercise Prescription bridges the gap between research and practice for fitness professionals. Its unique scope, depth of coverage, and clearly outlined approach make it a valuable resource for students and exercise science professionals to increase their knowledge, skill, and professional
Competence
Inhoudsopgave : Chapter 1. Physical Activity, Health, and Chronic Disease Chapter 2. Preliminary Health Screening and Risk Classification Chapter 3. Principles of Assessment, Prescription, and Exercise Program Adherence Chapter 4. Assessing Cardiorespiratory Fitness Chapter 5. Designing Cardiorespiratory Exercise Programs Chapter 6. Assessing Muscular Fitness Chapter 7. Designing Resistance Training Programs Chapter 8. Assessing Body Composition Chapter 9. Designing Weight Management and Body Composition Programs Chapter 10 Assessing Flexibility Chapter 11. Designing Programs for Flexibility and Low Back Care Chapter 12. Assessing Balance and Designing Balance Programs
Keywords: Fitness